ANALISIS PROBLEMATIK PENGELOLAAN DANA HAJI DIKANTOR KEMENTRIAN DEPARTEMEN AGAMA SUMATERA UTARA - Uswatun Hasanah Harun; Maryam Batubara; Muhammad Arif (ITB AAS INDONESIA, 2023)
The Hajj Fund Financial Management Agency at the Ministry of Religious Affairs in North Sumatra is a general policy that becomes the basic concept of the Hajj Finance Management Agency in carrying out Hajj Fund Management as stated in Law Number 34 of 2014, Government Regulation Number 5 of 2018, In implementing the management of hajj funds requires organizational governance that is in accordance with the duties and provisions. The purpose of this study is to find out the analysis of the problematics of managing hajj funds, solving problems of the phenomenon and knowing the strategies and benefits in managing hajj funds. By using a qualitative approach with a descriptive method. Descriptive method is used to provide an overview/explanation of a problem. The implementation of Hajj Fund management for Problem Solving at the Hajj Financial Management Agency in North Sumatra has been maximally completed in collaboration with other institutions in accordance with the mission and vision of the Ministry of Religion in North Sumatra, which is to improve the Quality of Hajj Services.